(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Ano-rectal disorders are on exponential growth in the population of mankind, with bleeding per anum as one of the main prodromal symptom. Just like the metabolic or lifestyle disorders namely diabetes mellitus, hypertension, ano-rectal disorders also owe their etiology to irregular & improper diet, sedentary lifestyle, prolonged sitting in inaccurate postures, improper bowel habits & also psychosocial factors. In Ayurveda, Sushruta has described it vividly in Arsha nidanam that those people suffering from Mandagni i.e., reduced digestive power which leads to Vata aggravation alone or in combination with other Dosas and manifests itself with symptoms like bleeding per anum, pain, irritation, discharge in the Guda. In modern science, excessive straining, increased abdominal pressure and hard stools are told to be the etiology of symptomatic haemorrhoids as these causes leads to increased venous engorgement of the haemorrhoidal plexus and cause of prolapse of haemorrhoidal tissue. Bleeding, thrombosis and symptomatic haemorrhoidal prolapse may result. Some of the ano-rectal disorders mentioned by Sushruta are Arsha, Parikartika, Bhagandara.